A Critical Review on the Voltage Requirement in Hybrid Cells with Solar Energy Harvesting and Energy Storage Capability. Issue 2 (10th November 2020) - Takshi, Arash; Aljafari, Belqasem; Kareri, Tareq; Stefanakos, Elias
Abstract: Energy storage is essential in many electrical and electronic applications powered through solar cells. This has motivated many research groups around the world to design single hybrid cells with the capability of both energy harvesting and charge storage. Despite the general perception of being able to make more compact and lower‐cost solar panels with hybrid cells, as compared to conventional energy systems with separated panels and batteries, there are drawbacks in the series connection of hybrid cells in a panel form. These drawbacks are discussed in this review. The focus of the current manuscript is on the application of single hybrid cells in low‐voltage and low‐power electronics and wearable electronics. The voltage requirements in those applications are discussed and two‐terminal and three‐terminal hybrid cells are reviewed. Promising technologies are highlighted in the conclusions. Abstract : Harvest and store : This review paper focuses on the market potential for hybrid solar cell‐energy storage devices and addresses the voltage requirement to use hybrid cells for low‐power and low‐voltage electronics.